Effect of Loan Default on Financial Performance of Microfinance Insitutjons in Embu County: A Case Study of Bimas Limited- Embu County - Ogero, Simon Caleb (University of Embu, 2019)
This study ought to assess the effects of loan default on financial performance of microfinance institutions in Embu. The study attempts to provide means by which microfinance institutions in Embu County such as BIMAS will reduce loan default andimprove financial performance. The study has three objectives which are to identify causes of 1'oan de1;tult by MFls' clients, identify ways loan officers can use to ensure loan repayment is done on time. Give recommendations microfinance institutions could use to ensure loan repayment as scheduled and finally identify the costs of loan default on financial performance of microfinance institutions. Objectives were achieved through data collected from BIMAS by use of questionnaire for both Loan Officers and clients. The data collected was analyzed using SPSS version 22. :The findings from the study indicated that diversion of funds to unintended purpose, inability to' generate enough profits from business, high interest rates and clients having multiple loans affect' the ability to repay loans on time. Microfinance institutions to have proper loan appraisal, adequate monitoring of loans, use of third-party guarantors and have appropriate lending procedures' to minimize loan default. In conclusion, loan default had negative effect on fina;1cial performance of microfinance institutions (Birnas Limited) and their sustainability.